The Modus of Beggars in Lampung Urban Area : An Islamic Law Perspective - Khoirul Abror; Suhairi Suhairi; A. Kumedi Ja'far (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
The poor and underprivileged are people who must be considered by the Government, but the reality at this time is that there are many poor and underprivileged people who become professions in the city of Bandar Lampung and Metro City, so it is necessary to review the existence and factors that influence it. This review is a field research (field research) conducted in Bandar Lampung City and Metro City; by describing data obtained through observation, in-depth interviews; the method used in analyzing is qualitative analysis presented descriptively; the aim is to find factors that drive the existence of beggars in urban areas, and the mode used by urban beggars. The existence of beggars in the city of Bandar Lampung and the city of Metro both at the intersection of red lights and in the mall yard, the courtyard of the mosque and the home visit is a mode to get easy income, the main factor that drives the existence of beggars in the city of Bandar Lampung and Metro City due to income that is not fulfilling the necessities of life, the attractiveness factor of work that is easy, practical, influenced by the sympathies of potential benefactors, and relatively large income; various modes undertaken by beggars to attract the sympathy of the community, including bringing children who are still toddlers, pretending to be blind and lame, employing elderly parents (elderly), dressing all worn out, and pretending to smear that does not heal ; The existence of beggars in the city of Bandar Lampung and the city of Metro both at the intersection of red lights and in the mall yard, the courtyard of the mosque and the home visit is a mode to get easy income, the main factor that drives the existence of beggars in the city of Bandar Lampung and Metro City due to income that is not fulfilling the necessities of life, the attractiveness factor of work that is easy, practical, influenced by the sympathies of potential benefactors, and relatively large income; various modes undertaken by beggars to attract the sympathy of the community, including bringing children who are still toddlers, pretending to be blind and lame, employing elderly parents (elderly), dressing all worn out, and pretending to smear that does not heal.